PENGARUH EXPERIENTIAL MARKETING TERHADAP KEPUASAN PELANGGAN STARBUCKS COFFEE SHOP - prihastuti, dyah rini; wahyu wicaksono, adreas fadly (Fakultas Ekonomi dan Bisnis, Universitas 17 Agustus 1945 Surabaya, 2017)
ABSTRACTExperiential Marketing can create an advantage for the producer because the sale is not a product or service but a pleasant experience, so that the products and services have more selling value compared to competitors although offered the same. (source: Yuliastuti and Palupi, 2004). This difference that makes customers willing to pay dearly with pleasure and without feeling compelled to get the desired product or service. These experiences are decisive for customer satisfaction and create their own brand loyalty. Customer satisfaction is very important for the life of a business, if what the customer receives in accordance with expectations then the customer will feel satisfied and re-buy and if the customer receives that is not appropriate or are below expectations then the customer will feel dissatisfied. Therefore, every business must pay attention to the customer and if the customer is satisfied then indirectly the customer will become a free marketing force for the company's business. The purpose of this study is to determine the effect of experiential marketing on customer satisfaction. The object of this research is Starbucks Coffe. The result of data analysis shows that there is a significant influence together between experiential marketing variables (sense (X1), feel (X2), think (X3), act (X4) and relate (X5)) to customer satisfaction (Y) it is known from the calculated value of the F test that has a significance value of 0.000 below 0.05. Partial test results also show the influence of sense (X1), feel (X2), think (X3), act (X4) and relate (X5) to customer satisfaction (Y) with t test significance value less than 0.05. The amount of influence of all variables on customer satisfaction (Y) is 83.6%, while the rest of 16.4% is caused by other variables not examined in this study. With this result the first hypothesis of research is accepted truth.Â Kata Kunci : Experiential Marketing, Kepuasan Pelanggan.Â